Compendium of Evaluation Studies 1999-2006 4th Volume - Planning Commission (Planning Commission, 2006)
The Scheme of the Short Stay Homes for Women and Girls launched in 1969 is designed to provide temporary shelter to women and girls who are in social and moral danger due to family problems, mental strain, violence at home, social ostracism, exploitation and other causes. The scheme provides a package of services to the inmates, such as: medical care, psychiatric treatment, case work services, occupational therapy, educational-cum-vocational training, recreation facilities and rehabilitation. The scheme is being executed through non-governmental organizations (NGO) in different parts of the country. The NGOs receive grants from the Department of Women and Child Development, Ministry of Human Resources Development, Government of India.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission